2015
DOI: 10.1016/j.jvs.2014.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Gender and racial differences in endothelial oxidative stress and inflammation in patients with symptomatic peripheral artery disease

Abstract: Background We compared (a) cellular reactive oxygen species (ROS) production, inflammation, and apoptosis of cultured endothelial cells treated with sera, and (b) circulating inflammatory, antioxidant capacity, vascular biomarkers, and calf muscle hemoglobin oxygen saturation (StO2) in men and women with PAD. A secondary aim was to compare exercise performance and daily ambulatory activity between men and women. We hypothesized that women would have more impaired endothelial cellular ROS, inflammation, and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 39 publications
4
43
1
1
Order By: Relevance
“…Acute and chronic stress can induce microglial cell mediated immune activation and inflammation in the brain, and recent studies have demonstrated sex differences in microglial density, function, and morphology in several brain regions 27 . Sex-specific association of oxidative stress and inflammation is also observed in other vascular-related diseases 10 . Since the levels of biomarkers were similar between males and females in our sample, it is plausible that female survivors of ALL may be more sensitive, with a lower physiologic threshold to the effects of chronic inflammation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Acute and chronic stress can induce microglial cell mediated immune activation and inflammation in the brain, and recent studies have demonstrated sex differences in microglial density, function, and morphology in several brain regions 27 . Sex-specific association of oxidative stress and inflammation is also observed in other vascular-related diseases 10 . Since the levels of biomarkers were similar between males and females in our sample, it is plausible that female survivors of ALL may be more sensitive, with a lower physiologic threshold to the effects of chronic inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…Given evidence to suggest sex-specific associations of oxidative stress and inflammation with vascular-related diseases in the general population 10 , as well as sex differences in reports of fatigue and sleep in cancer patients 3 , all analyses were stratified by sex. For descriptive purposes, neurocognitive, behavioral, and fatigue outcomes were transformed into age-adjusted Z-scores (mean=0, standard deviation=1.0) using national normative data.…”
Section: Methodsmentioning
confidence: 99%
“…The authors computed the ratio of walking events to upright events to provide an Event-Based Claudication Index and reported that this index was greater in PAD patients with intermittent claudication than in controls. Other studies reported associations in PAD patients between walking pattern and clinical, physiological, or biological features (Gardner et al, 2010b(Gardner et al, , 2010c(Gardner et al, , 2011b(Gardner et al, , 2012b(Gardner et al, , 2014cRitti-Dias et al, 2011;Gardner et al, 2015).…”
Section: Characterization Of Ambulatory Walking Patternmentioning
confidence: 98%
“…We have previously shown that numerous outcome measures are different between men and women with PAD, as women have greater impairment in baseline ambulation [15], vascular function [16], and inflammation [17]. Furthermore, women, particularly those with diabetes, have less increase in COT and PWT following supervised exercise training [18, 19], even though their increase in 6-minute walk distance (6MWD) following a home-based exercise program was similar [10].…”
Section: Introductionmentioning
confidence: 99%